Development and testing of an opioid tapering self-management intervention for chronic pain: I-WOTCH - Kirstie Haywood; Martin Underwood; Anisur Rahman; Kate Seers; Andrea D Furlan; Dipesh Mistry; Charles Abraham; Harbinder Kaur Sandhu; Sharisse Alleyne; Shyam Balasubramanian; Lauren Betteley; Katie Booth; et al. (BMJ Open, 2022)
Objectives To describe the design, development and pilot of a multicomponent intervention aimed at supporting withdrawal of opioids for people with chronic non-malignant pain for future evaluation in the Improving the Wellbeing of people with Opioid Treated CHronic pain (I-WOTCH) randomised controlled trial.Design The I-WOTCH intervention draws on previous literature and collaboration with stakeholders (patient and public involvement). Intervention mapping and development activities of Behaviour Change Taxonomy are described.Setting The intervention development was conducted by a multidisciplinary team with clinical, academic and service user perspectives. The team had expertise in the development and testing of complex health behaviour interventions, opioid tapering and pain management in primary and secondary care, I.T programming, and software development—to develop an opioid tapering App.Participants The I-WOTCH trial participants are adults (18 years and over) with chronic non-malignant pain using strong opioids for at least 3 months and on most days in the preceding month.Outcomes A multicomponent self-management support package to help people using opioids for chronic non-malignant pain reduce opioid use.Interventions and results Receiving information on the impact of long-term opioid use, and potential adverse effects were highlighted as important facilitators in making the decision to reduce opioids. Case studies of those who have successfully stopped taking opioids were also favoured as a facilitator to reduce opioid use. Barriers included the need for a ‘trade-off to fill the deficit of the effect of the drug’. The final I-WOTCH intervention consists of an 8–10 week programme incorporating: education; problem-solving; motivation; group and one to one tailored planning; reflection and monitoring. A detailed facilitator manual was developed to promote consistent delivery of the intervention across the UK.Conclusions We describe the development of an opioid reduction intervention package suitable for testing in the I-WOTCH randomised controlled trial.Trial registration number ISRCTN49470934.